CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, FIRM SIZE, DIVIDEND PAYOUT RATIO, AND GREEN ACCOUNTING ON STOCK RETURN IN LQ45 COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2017-2021 PERIOD - ,; ,; ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 8 No 4 (2024): Bilancia : Jurnal Ilmiah AkuntansiDO - 10.35145/bilancia.v8i4.4694, 2024)
The purpose of this study was to determine the effect of the current ratio, debt-to-equity ratio, return on equity, firm size, dividend payout ratio, and green accounting on stock returns of LQ45 companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses a quantitative approach. The population in this study were all LQ45 companies listed on the IDX for the 2017-2021 period, totaling 45 companies. Using the purposive sampling method, the sample in this study was set at 45 companies. The data collection technique in this study is to use the documentation method. Data analysis using regression with the help of Smart PLS. The results of this study indicate that the current ratio, debt-to-equity ratio, return on equity, firm size, and green accounting have no significant negative effect on stock returns, while the dividend payout ratio has a significant negative effect on stock returns of LQ45 companies listed on the Stock Exchange Indonesia for the 2017-2021 period. Suggestions for companies are expected to be able to manage each of the company's assets to gain profits so that they can increase stock prices which will affect the company's stock returns. Tujuan penelitian ini adalah untuk mengetahui pengaruh current ratio , debt to equity ratio , return on equity , firm size , dividend payout ratio , dan green accounting terhadap return saham perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia periode 2017-2021. Penelitian ini menggunakan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh perusahaan LQ45 yang terdaftar di BEI periode 2017-2021 yang berjumlah 45 perusahaan. Dengan menggunakan metode purposive sampling, sampel dalam penelitian ini ditetapkan sebanyak 45 perusahaan. Teknik pengumpulan data dalam penelitian ini adalah dengan menggunakan metode dokumentasi. Analisis data menggunakan regresi dengan bantuan Smart PLS. Hasil penelitian ini menunjukkan bahwa current ratio, debt to equity ratio, return on equity, firm size, dan green accounting tidak berpengaruh negatif signifikan terhadap return saham, sedangkan dividen payout ratio berpengaruh negatif signifikan terhadap return saham perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia periode 2017-2021. Saran bagi perusahaan diharapkan dapat mengelola setiap aset perusahaan untuk memperoleh laba sehingga dapat meningkatkan harga saham yang akan mempengaruhi return saham perusahaan.